The object at hand. - Park, Edwards (Smithsonian)
Looks back to the birth of computers with a machine invented by Charles Babbage during the 19th century. Babbage's personal background and invention; Georg and Edvard Scheutz, builders of the `Difference Engine' displayed at the National Museum of American History and using Babbage's concepts.